Giải bài toán Carleman suy rộng trên trục thực bằng phương pháp chiếu lặp trên cơ sở phép chiếu bình phương tối thiểu - Quang, Le Xuan (Journal of Computer Science and Cybernetics, 2018)
In this paper the projection iterative method is used for solving the generalized Carleman problem A(t) F+(t) + B(t) F+(-t) + C(t) F-(t) = h(t), tÎR Where R is the real axis; A(t), B(t), C(t) are Holder continuous functions; h(t)ÎL2, and F+(t), F-(t) is a boundary value of analytic function upper (lower) half-plane.